Rapid and Reliable Assessment of Fish Physiological Condition for Fisheries Research and Management Using Fourier Transform Near-Infrared Spectroscopy - Goldstein, Esther D.; Helser, Thomas E.; Vollenweider, Johanna J.; Sreenivasan, Ashwin; Sewall, Fletcher F. (Frontiers in Marine Science, 2021)
Measuring fish population responses to climate change requires timely ecological information, warranting innovative approaches to data collection in fisheries research and management. Fourier transform near-infrared (FT-NIR) spectroscopy is a promising tool to efficiently and cost-effectively obtain multiple types of fisheries data including fish physiological health and energetics that can provide indicators of stock status and environmental change. We tested the applicability of FT-NIR spectroscopy to determine fish physiological state and condition by developing calibration models for morphometric indices of body condition [Fulton’s K and hepatosomatic index (HSI)], biochemical measurements of tissue composition (lipid content and energy density), and a nucleic acid-based index of recent growth (RNA:DNA) of juvenile Pacific cod (Gadus macrocephalus). Calibration models had the best predictive ability for lipid content followed by HSI and energy density, whereas spectral data had weak relationships with Fulton’s K and RNA:DNA. For lipid content, energy density, and HSI, informative spectral regions were primarily associated with carbon-hydrogen bonds in lipid molecules. Additionally, FT-NIR spectroscopy calibration models better predicted lipid content than morphometric measurements that are often used as proxies for measuring energy reserves, indicating that FT-NIR spectroscopy might serve as a more informative index of body condition and energy stores than other rapid methods. Efficient sample analysis by FT-NIR spectroscopy can supplement traditional metrics of body condition and be especially useful for ensuring the availability of monitoring data in support of fisheries research and management.